Potensi Antifungi Bakteri Asam Laktat dari Saluran Pencernaan Ayam Kampung terhadap Kapang Aspergillus flavus - Natasia, Novera; Jannah, Siti Nur; Rukmi, MG Isworo (Bioma : Berkala Ilmiah Biologi, 2020)
Contamination of Aspergillus flavus can attacks food and feed ingredients, especially seeds during the storage. The using of biological agents, like microbes that have antifungal activity becomes a promising and important solution to be studied. This research aims to find out the antifungal activity of lactic acid bacteria (LAB) from digestive tract of â€œKampungâ€ chickens against the growing of A. flavus. Source ofÂ  the isolates are from colon, ventriculus, and crop. The inoculums of LAB which using were suspension of cell and cell free supernatant (CFS). There were 6 isolates of LAB (Bub1, Bub3, Bub4, V52, C51, and NNB) tested to obtain the potential of antifungal activity, by with well diffusion and and submerged culture method. The results showed that the 5 isolates suspension cell of LAB showed inhibitory zones, except Bub1, whereas all CFS LAB showed the inhibitory zones against the growth of A. flavus in MRSA medium.Â  Furthermore, antifungal activity of LAB against A. flavus to be observed by measuring the dry weight of the mycelium production, as well as the percentage of inhibition during the incubation period. All isolates of LAB, from suspension cell and CFS showing antifungal activity against growth of A. flavus. The Bub3 and NNB isolates, from suspension cell and CFS showed that the best antifungal activity compared to the others.